Comprehensive Evaluation of Examination Quality Based on Fuzzy AHP - Linlin Liu; Hong Chen; Ruixin Zhang (Institute of Advanced Engineering and Science, 2013)
Examination is undoubtedly one of good means to evaluate what and how much the examinees have mastered. Effective evaluation of the quality of curriculum examination will not only contribute to scientifically testing the students’ mastery of the knowledge but also help instruct the teachers to set scientific tests. This paper establishes the evaluation indexes of curriculum quality, calculates the weight of them, and gives effective evaluation of the quality of course examination by using the fuzzy AHP comprehensive evaluation, which has practical values in improving the efficiency of teaching evaluation. The research for the examination quality evaluation system is to accurately reflect and describe the rationality of examination quality index system so as to improve the rationalization level of examination papers. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3295